2015
DOI: 10.1183/13993003.00724-2015
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline in the treatment of multidrug- and extensively drug-resistant tuberculosis

Abstract: Bedaquiline, a diarylquinoline, improved cure rates when added to a multidrug-resistant tuberculosis (MDR-TB) treatment regimen in a previous placebo-controlled, phase 2 trial (TMC207-C208; NCT00449644). The current phase 2, multicenter, open-label, single-arm trial (TMC207-C209; NCT00910871) reported here was conducted to confirm the safety and efficacy of bedaquiline.Newly diagnosed or previously treated patients with MDR-TB (including pre-extensively drug-resistant (pre-XDR)-TB or extensively drug-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
236
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(254 citation statements)
references
References 27 publications
(37 reference statements)
8
236
3
7
Order By: Relevance
“…In mice, Rv0678 resistant mutants may be selected with 8 weeks of bedaquiline monotherapy (D. Almeida, unpublished observation) but emerge only late in the course of combination therapy and are eventually cleared, presumably by the action of companion agents (6). Clinically, these mutants emerged almost entirely among patients with pre-XDR-and XDR-TB (6), but their isolation has not clearly been associated with poorer clinical outcomes among patients receiving bedaquiline with more effective companion agents (28). These results underscore the importance of appropriate combination therapy and adherence and the risk of premature discontinuation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, Rv0678 resistant mutants may be selected with 8 weeks of bedaquiline monotherapy (D. Almeida, unpublished observation) but emerge only late in the course of combination therapy and are eventually cleared, presumably by the action of companion agents (6). Clinically, these mutants emerged almost entirely among patients with pre-XDR-and XDR-TB (6), but their isolation has not clearly been associated with poorer clinical outcomes among patients receiving bedaquiline with more effective companion agents (28). These results underscore the importance of appropriate combination therapy and adherence and the risk of premature discontinuation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although encouraging initial observations have been made of faster culture conversion in early bactericidal activity and phase 2 studies of bedaquiline, 365,366 and high rates of culture conversion in French 367 and South African patients with XDR tuberculosis (100% in the French cohort and 85% in the South African cohort), 324 another analysis 368 indicated that the 120-week culture conversion rate was 70% in patients with pre-XDR tuberculosis and 62% in XDR tuberculosis when bedaquiline was used with companion drugs and an optimised background regimen. Thus, even with newer drugs such as bedaquiline, treatment failure will be common in patients with XDR tuberculosis or those with resistance beyond XDR tuberculosis, for which no effective therapy is available and so it remains programmatically incurable.…”
Section: Bedaquilinementioning
confidence: 99%
“…Preliminary DST methodology for bedaquiline was previously piloted and then used in two phase II clinical studies (3)(4)(5)(6). In these studies, bedaquiline DST was performed by 7H11 agar dilution and 7H9 broth microdilution methods using the resazurin microtiter assay (REMA) (11,12).…”
mentioning
confidence: 99%
“…Bedaquiline, a diarylquinoline antimycobacterial (2), has received accelerated/conditional approval for use based on phase II trials in the United States (2012), the European Union (2014), and 7 countries with high MDR-TB burden (3)(4)(5)(6)(7)(8). Interim policy guidance for the use of bedaquiline as part of combination therapy for adults who have pulmonary MDR-TB has been issued by the World Health Organization (WHO) and the U.S. Centers for Disease Control and Prevention (CDC) (9,10).…”
mentioning
confidence: 99%